High prevalence of type 2 diabetes in Iraqi and Swedish residents in a deprived Swedish neighbourhood - a population based study - Sundquist Jan; Groop Leif; Agardh Carl-David; Johansson Sven-Erik; Bennet Louise; Råstam Lennart; Sundquist Kristina (BMC, 2011)
Abstract Background Immigrants from the Middle-East are at high risk of developing type 2 diabetes (T2D). The aim of the present survey was to measure, in a single deprived neighbourhood, the prevalence rates of impaired fasting glucose (IFG), impaired glucose tolerance (IGT) and T2D in residents originating from Iraq and to compare them to those in residents born in Sweden. An additional aim was to identify metabolic, lifestyle and socioeconomic risk factors associated with IFG/IGT and T2D in these residents. Methods The study was conducted February 1'st to March 31'st 2010. Men and women aged 45 to 65 years of Swedish or Iraqi origin, living in the neighbourhood of Rosengård, Malmö, Sweden, were randomly selected from the census register. Each participant signed a written informed consent form, underwent a physical examination and an oral glucose tolerance test (OGTT), provided blood samples and filled in a questionnaire. A total of 175 subjects participated (Swedish origin n = 79, Iraqi origin n = 96), reflecting an overall response rate of almost 60%. Results In total, 21.9% and 19.0% of the Iraqi and Swedish participants, respectively, suffered from T2D, while 24.0% of the Iraqi participants and 25.3% of the Swedish participants had IFG/IGT. There were no significant differences in prevalence rates relating to country of origin. Obesity (BMI ≥30 kg/m2) and sedentary leisure time physical activity were highly prevalent in both groups, while a family history of diabetes was more prevalent in participants from Iraq (49.2%) than in those from Sweden (22.8%) (p = 0.001). Being obese or having a sedentary leisure time were, independently associated with T2D (OR 5.43 (95% CI 2.10-14.02) and 2.89 (95% CI 1.03-8.10) respectively), while economic difficulties were independently associated with IFG/IGT (OR 2.55 (95% CI 1.06-6.15)) after adjustment for the confounding effects of other common risk factors for T2D. Conclusions This study reveals a high prevalence of T2D, independently of country of origin (Iraq or Sweden), in a socially vulnerable area and additionally presents a risk factor profile that is markedly different from that of Sweden in general.